1997
DOI: 10.1007/s004330050076
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium based hypo-osmolality on arterial smooth muscle reactivity in vitro

Abstract: The study tested the hypothesis that the reduced [Na+]e and hypo-osmolality of normal pregnancy are causally linked to the attenuation of vascular smooth muscle reactivity in vitro. Aortic rings from nonpregnant female rats were incubated in physiological medium containing 114 mM NaCl/l and the contractile responses to phenylephrine, KCl and CaCl2 as well as the relaxations to acetylcholine and KCl were compared with those of rings incubated in normal medium containing 119 mM NaCl/l. There was no solute substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Thus, in the present study, we determined the vasodilatory effect of increased glucose concentration in isolated and perfused mouse Af-Arts with preconstriction, and our results demonstrated that an increase in glucose level dilated Af-Art. Additionally, because the osmolality could affect vascular reactivity (20,65), L-glucose, the enantiomer of D-glucose, was used to balance the osmolality as control. Our results demonstrated that same concentration of L-glucose had no significant effect on the diameter of Af-Art, which indicates that the high glucoseinduced vasodilation of Af-Art was independent of the alteration in osmolality.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present study, we determined the vasodilatory effect of increased glucose concentration in isolated and perfused mouse Af-Arts with preconstriction, and our results demonstrated that an increase in glucose level dilated Af-Art. Additionally, because the osmolality could affect vascular reactivity (20,65), L-glucose, the enantiomer of D-glucose, was used to balance the osmolality as control. Our results demonstrated that same concentration of L-glucose had no significant effect on the diameter of Af-Art, which indicates that the high glucoseinduced vasodilation of Af-Art was independent of the alteration in osmolality.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotonicity of the extracellular environment occurs in several situations including reduced extracellular Na ϩ concentration seen in normal pregnancy (11), overhydration following intense exercise (1,12), and treatment with citalopram (15). Other hyposmotic states are found in situations involving deficits in plasma proteins secondary to hepatic dysfunction and nutritional deficits.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the in vitro findings reported by Thoren, we showed in vivo that baroreceptor discharge in anesthetized pregnant rats increased in the initial minute of a step pressure increase but appeared to adapt or decay more rapidly in pregnant compared with virgin rats during the 10-min exposure to a step pressure stimulus (Hines, 2000). Hyponatremia has also been shown to decrease vascular responsiveness to pressor agents in aortic rings from female rats, suggesting that hypoosmolality could decrease baroreceptor discharge through effects on vessel wall distension during increases in pressure as well as via direct effects on cell discharge (Ezimokhai & Osman, 1998).…”
mentioning
confidence: 99%